2-State Current Characteristics of MOSCAP with Ultrathin Oxide and Metal Gate. (6th November 2015) - Tan, Yu-De; Hwu, Jenn-Gwo
Abstract : By using the combination of thin metal gate and ultra-thin oxide, metal-oxide-semiconductor (MOSCAP) structure exhibits distinct 2-state characteristic in reading currents. The gate electrode is long and thin so that it owns a larger gate resistance to enlarge the RC time response. The device exhibits a retention time constant of about 210 ms, and an endurance of at last one million cycles. However, the control sample does not exhibit the similar behavior. It is believed that the concept of using thin metal gate and ultra-thin oxide is applicable to scaled structure since they are controllable factors in design.